Enhanced flexible pavement subgrade stability using activated carbon, coir fiber, and lime - Tamassoki, Sakina; Wang, Shanyong; Nik Daud, Nik Norsyahariati; Roshan, Mohammad Jawed (Chinese Academy of Sciences, 2025)
This study presents a method for improving flexible pavement subgrades using activated carbon and lime as stabilizers and coir fiber as reinforcement, improving subgrade performance using natural and recycled materials. Two residual soil types, Soil 1 and Soil 2, were examined for enhanced mechanical properties using California bearing ratio, indirect shear, direct shear, and consolidation tests. Pavement design calculations were performed using the empirical method, and finite element modeling was employed to assess the impact of water levels on subgrade settlement and strain ratios. The findings revealed notable improvements in cohesion and tensile strength when lime, activated carbon, and coir fiber were used for stabilization, achieving increases of up to 128.9 % and 167.71 % for Soil 1, and 155 % and 3045.86 % for Soil 2, respectively. Moreover, these stabilized samples exhibited the lowest penetration rates, recording values of 0.2 for both soils after 20 loading cycles. Incorporating a stabilized subgrade reduced the required subbase thickness by up to 90.91 % compared to the untreated condition. Finite element modeling indicated that the high-permeability Soil 1 sample experienced an average settlement of 70.12 mm under repeated loading, which is 2.46 times higher than the 28.54 mm observed in the low-permeability sample. Finally, strain ratio analysis confirmed that adding stabilizers effectively reduced the subgrade strain, bringing the strain ratio below one and thereby meeting the road subgrade standard. These findings highlight the innovative use of coir fiber, activated carbon, and lime as high-performance stabilizers for flexible pavement applications, offering a practical solution for infrastructure development.